User Experience Design Manifesto - Maldonado, Paulo (2020)
The rapid change of the elements of context requires an urgent reflection on "Experience" and "Meaning with Value". The aim of this article is to critically review the User Experience Design (UXD) as a disciplinary field, and contribute by a Manifesto to an inspiring vision of the future. Some authors will be reviewed in order to list and discuss the different ideas to redefine the desirable skills to an enlightened practice and to influence a new ethos of "Be Innovation" to a better world. The article retrieves and revisits a Design Manifesto made on the basis of a strategic vision for Design based on distinctive design competencies. This Manifesto was in the origin of the platform www.inspaedia.com.